The impact of COVID-19 pandemics, perceived stress, and self-regulation of Chinese international students - Ting, Siu-Man Raymond; Liu , Zhiqi Angel (Journal of International Students, 2024)
In this study, we explore the perceived stress and self-regulation of four Chinese international students (CISs) at a public research university in the southeastern United States (U.S.) during the COVID-19 pandemic through individual semi-structured interviews. The identified themes include travel restrictions and delayed required tests, mixed experiences after arrival, differences in education systems, inadequate English preparation and performance, cultural and living adjustments, and limited self-care and coping strategies. The implications of these findings emphasize the importance of self-regulation, a deeper understanding of the challenges faced by international students, and considerations for related policy and practice, as well as directions for future research.